Cultural Influences on Learners' Attitudes toward English Pronunciation: A Comparative Study - Nelson Balisar Panjaitan; Yenni Christina (Acuity: Journal of English Language Pedagogy, Literature and Culture, 2025)
This study explores the attitudes of 91 students at Universitas Advent Indonesia toward English pronunciation in the context of language learning. Using Likert scale questionnaires, the research examines the perceived importance of pronunciation, preferences for pronunciation models, confidence levels, and how cultural identity shapes these attitudes. Students' views on teaching methods, including technology-enhanced instruction and feedback mechanisms, are also analyzed. The findings underscore a strong acknowledgment of pronunciation's role in effective communication, with significant support for interactive and culturally sensitive teaching approaches. Students expressed a preference for pronunciation models that align with their cultural identity, indicating a need for more personalized and contextually relevant instruction. This study provides valuable insights for language educators and curriculum developers, emphasizing the integration of students' cultural backgrounds into pronunciation pedagogy. Pronunciation remains a critical yet often underexplored component of English language learning, particularly in multilingual settings where cultural identity strongly influences learner attitudes. This study investigates the attitudes of 91 students at Universitas Advent Indonesia toward English pronunciation, addressing the broader issue of how cultural factors shape learners’ preferences and confidence in pronunciation. Employing Likert scale questionnaires, the research compares student responses across different ethnic and linguistic